2007
DOI: 10.1111/j.1468-1293.2007.00455.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved virological response to highly active antiretroviral therapy in HIV‐1‐infected patients carrying the CCR5 Δ32 deletion

Abstract: BackgroundPatients heterozygous for the C-C chemokine receptor 5 (CCR5) D32 deletion spontaneously progress less rapidly to AIDS and death than do wild-type patients. We investigated whether the CCR5 D32 deletion has an impact on immunological, virological and clinical responses to highly active antiretroviral therapy (HAART) in HIV-1-infected patients. Patients and methodsWe included in the study 565 HIV-1-infected patients from the French HIV-1 infected cohort with documented date of serconversion (SEROCO)/h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
4
12
1
Order By: Relevance
“…An array of factors influencing survival were analyzed in this study including demographics as well as clinical and immunological parameters. The frequency of the CCR5 Δ32/wt heterozygotes in this study was 14.0% and is consistent to the previous reports for Caucasian populations, while use of archived samples allowed to avoid the bias related to the survival benefit of the mutation in HIV infected patients who may have died [8], [19], [20]. The near-significant difference between the male and female gender frequency might be related to the transmission route – higher number of women was infected sexually.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…An array of factors influencing survival were analyzed in this study including demographics as well as clinical and immunological parameters. The frequency of the CCR5 Δ32/wt heterozygotes in this study was 14.0% and is consistent to the previous reports for Caucasian populations, while use of archived samples allowed to avoid the bias related to the survival benefit of the mutation in HIV infected patients who may have died [8], [19], [20]. The near-significant difference between the male and female gender frequency might be related to the transmission route – higher number of women was infected sexually.…”
Section: Discussionsupporting
confidence: 89%
“…No significant effect of the Δ32 allele, survival and AIDS free survival was also found by Laurichesse et al [8]. Moreover, Brumme et al, did not find the association between the CCR5 Δ32/wt genotype and time to virological failure in the study of 436 individuals observed for the median follow-up of 22 months [22].…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…When the polymorphic alleles were analyzed individually, CCR5-D32 carriage was associated with improved CD4+ T cell gain during HAART, confirming previous studies showing a protective effect of CCR5-D32 on other markers of disease progression of the HIV-1 infection during HAART [13,21,25,29,[48][49][50]. The CCR5-D32 allele is known to encode a truncated protein that is not expressed on cell surface.…”
Section: Discussionsupporting
confidence: 81%